Hubungan Indeks Massa Tubuh (IMT) dengan Kelincahan pada Pemain Futsal Hupernako FC U-15 - Muhammad Asrani; Rinna Ainul Maghfiroh (Universitas Nurul Jadid, 2025)
Futsal is a high-intensity intermittent sport that requires agility for rapid changes of direction and effective ball dribbling. Nutritional status, reflected by body mass index (BMI), may influence players’ agility. This study aimed to examine the association between BMI and agility among Hupernako FC U-15 futsal players. An analytic observational cross-sectional study was conducted involving 20 players aged 12–15 years selected through purposive sampling. BMI was calculated from body mass and height (kg/m²), while agility was assessed using the Illinois Agility Test. The association was analyzed using the chi-square test. The results showed a significant association between BMI category and agility (p=0.042). Conclusion: BMI is significantly related to agility in Hupernako FC U-15 futsal players; maintaining an optimal BMI should be considered in performance development.